The Species Diversity of Herpetofauna in The Border Area of Gunung Tilu Natural Reserve and Pusat Penelitian (PPTK), Gambung, Mekarsari Village, Ciwidey, West Java - Nasution, Ahmad Ramadhan; Maulana, Fadil; Fasha, Stiza Anindya; Ramadhine, Teghes Diva (Journal of Tropical Biodiversity, 2024)
The Tea and Quinine Research Center (PPTK), Gambung is located in Mekarsari Village, Pasir Jambu, District, Bandung, West Java. This location borders the Gunung Tilu Nature Reserve in West Java. The lack of information about herpetofauna in this area prompted this research. The study was conducted using the Visual Encounter System (VES) method on three different transects with distinct characteristics: the Situ Kubang transect, which is an area along the riverbank; the Abikarna transect, which is a forest transect along a small stream; and the Kebun transect around the Tea and Coffee Plantations. Data collection was carried out for three days, by recording: encounters of herpetofauna species, as well as their habitat components, including weather, temperature, air humidity, air pH and canopy cover. The results revealed 15 species from 9 families, including 5 amphibian families and 4 reptile families. The species diversity index (H’) of herpetofauna across the three transects was categorized as moderate. The Kebun transect had the highest Diversity Index (H’) value of 1.90, followed by the Situ Kubang transect with 1.78, and the Abikarna transect with H’ = 1.23. The herpetofauna species with the highest number of encounter was Chalcorana chalconota with 25 individuals, while other species had low number encounter, with fewer than 3 individuals per species, including Bronchocela jubata, Takydromus sexlineatus, Pseudocalotes tympanistriga, Gongylosoma baliodeirus, Limnonectes kuhlii, Fejervarya limnocharis, Polypedates leucomystax, Rhacophorus margaritifer, and Microhyla achatina. The species Bronchocela jubata, Leptobrachium hasseltii, and Chalcorana chalconota were found on all research transects.